Chasing Heideggerian circles: Freedom, call, and our educational ground. Issue 10 (24th August 2017) - d'Agnese, Vasco
Abstract: Over the last couple of decades, Heideggerian philosophy has become an important resource for educationalists. A growing body of literature has demonstrated its educational potential, thus illumining pivotal educational features and phenomena. Whereas my research is situated in the critical space opened by this literature, I adopt a slightly different perspective: in this paper, I discuss what we may refer to as the thoroughly educational nature of Heideggerian philosophy. I contend that Heideggerian thought is not only anchored by questions and features that are quintessentially pedagogical but also represents a passionate and ethical call to freedom, becoming and the space of the 'not-yet', a call that appeals to the self to overturn his gesture and position; a call that is, in and of itself, educational. Rather than abandoning the initiative towards Being, Heidegger, in the late 1920s, created an ethic of resoluteness and choice that places freedom and responsibility centre stage. Hence, when analysing Heidegger's thought, we need not necessarily place educational concerns and demands from without, nor must we necessarily apply Heideggerian insights to analyse educational features and phenomena, for Heideggerian philosophy is always already rooted in, and in a sense is, an educational endeavour.